Acceptance usage of telemedicine during and post Covid-19 pandemics in Malaysia - Mohd Hafiz, Ahmad Nasruddin (2021)
During Covid 19 pandemics, people having difficulties to enter healthcare facility as the risk of having covid 19 infection is very high. Due to that reason, the use of telemedicine seems to emerge as people need to get consultation from healthcare personnel to enable them to stay healthy. A study conducted to see the acceptance of Malaysian local to accept the use of telemedicine in private hospital in Malaysia. A data then collected from two main private hospital in Johor Bahru where 217 questionnaire distributed to the respondent and about 200 questionnaire were answered to make the conclusion to this study. The main objective of this study is to analyse the relationship of the acceptance usage of telemedicine in Malaysia between perceive usefulness, perceived ease of use and facilitating condition. This research study using the applicability of TAM with additional variables to look at the adoption of telemedicine services in Malaysia.. From the study conducted, it revealed that there is a positive relationship of acceptance usage of telemedicine in Malaysia with the perceive usefulness, perceived ease of use and facilitating condition. This study offer valuable information for policy makers and the stake holder in implementing telemedicine services